The Influence Of Psychoeducation On Knowledge And Attitudes On The Importance Of Asi As A Stunting Prevention Measure Among Caders In Rasau Jaya - Pratika Sari; Riszky Ramadhan; Selviana, Selviana (Sean Institute, 2024)
Stunting is a serious problem experienced by Indonesian children due to prolonged malnutrition. ASI (breast milk) has a significant role in preventing stunting. This research aims to find out whether there is an influence of psychoeducation on knowledge and attitudes about the importance of breastfeeding as an effort to prevent stunting in cadres. The approach used in this research is quantitative with experimental research methods. The type of experiment used is Pre-Experimental Design with the design approach